The Validity Test of Flipbook Learning Media in A Genetics Course Based on Local Wisdom in North Maluku - Roini, Chumidach; Suparman, Suparman; Rasyid, Magfirah; Herliani, Herliani; Sabtu, Rasmita; Ilmi, Zarobatul Lil (Universitas Sultan Ageng Tirtayasa, 2025)
Learning media plays a role in generating enthusiasm and interest in learning for students, so an interesting learning media is needed that can help students in the learning process. Flipbook is one of the interactive learning media that combines visual representation, narration, and interactive simulation that is expected to help students. The purpose of this study is to see the validity of the flipbook for genetics course produced from local species data of North Maluku. The study is a research and development study (Research and Development) which refers to the Thiagarajan 1974 development model, namely 4D (Define, Design, Develop, and Disseminate). The results showed that the flipbook learning media was very valid for use in learning with a percentage of 92% from material, media and language experts in this case by lecturers, and 98% from material, media and language experts in this case by teachers. The level of practicality of the learning media flipbook has a percentage of 91% obtained from student responses. This means that flipbook learning media is very valid and very suitable for use